The Contribution of Zakat, Infaq, Sadaqa, and Waqf (Ziswaf) Strategic Management in Developing the Prosperity of Ummah (Universitas Pembangunan Nasional Veteran Jakarta, 2023)
As a country with the largest muslim population in the world, Indonesia is still far behind in developing the potential of zakat, infaq, sadaqa, and waqf (ziswaf) which should be optimized. This requires a mature strategy in managing to maximize the potential of ziswaf. This study aims to examine the development of ziswaf strategic management at the Baitul Al-Qur'an Social Fund Institution (LDSBQ) which has a vision and mission based on Islamic sharia and aims to prosper the Ummah. This research uses a qualitative approach with a descriptive analysis method, while the data collection instruments use interviews, observation, and documentation. Sources were taken from various references related to the topic of the problem, namely journals, books, and other articles. The results showed that the three main programs of LDSBQ are First, scholar smile; engaged in education. Second, smile healthy; is engaged in the health sector. Third, independence smile; which is a movement for community independence in the economic field, and is supported by social-religious activities such as waqf and da'wah programs. While the fundraising strategy uses a potential network of student and teacher guardians, a network of Gontor alumni colleagues, program socialization through social media, online and offline donation services, and program-based waqf. With a real sector-based movement, social community activities can have a significant impact on the welfare of the ummah to gain happiness in this world and the hereafter.